Selling exports to consumers in Bulgaria: Attitudes towards foreign products - Ziamou, P.; Zotos, Yorgos; Lysonski, S.; Zafiropoulos, C. (My University, 1999)
The continuing political and economic transformation in Eastern Europe has created a timely need for exploring profitable opportunities in East European markets. This paper responds to this need to develop 'marketing strategies for an expanding Europe.' The purpose of this paper is to assess the competitiveness of European Union (EU) products in Bulgaria. Specifically, this study aims at exploring Bulgarian consumers' perceptions of German, Greek, Italian, and Turkish products and their likelihood of purchasing these products. The construct of country-of-origin is used for this analysis since it is a powerful variable that can be used to gain competitive advantage in international marketing. The results clearly show that Bulgarians are more receptive to products from some countries compared to others but this does not correlate with purchase intentions. Implications and areas for further research are discussed.
Keywords: Wounds and Injuries; Firearms; Firearm injuries